2013
DOI: 10.1016/s1995-7645(13)60010-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and haemato-biochemical profile of Anaplasma marginale infection in dairy animals of Punjab (India)

Abstract: PCR is far more sensitive in detecting the disease even in latent infection which may act as nidus for spread of anaplasmosis to susceptible animals in endemic areas. Severity of anaemia and liver dysfunction were comparable both in patent as well as latent infection indicating pathogenicity of both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
24
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 17 publications
11
24
4
Order By: Relevance
“…[13], whereas Ashuma et al . [14] found prevalence of anaplasmosis to be on higher side (11.25%) as compared to the present study (4.17%). As there was no previous report of anaplasmosis from TVCC, Hisar, Haryana, in the recent past, so the disease can be categorized under the emerging status.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…[13], whereas Ashuma et al . [14] found prevalence of anaplasmosis to be on higher side (11.25%) as compared to the present study (4.17%). As there was no previous report of anaplasmosis from TVCC, Hisar, Haryana, in the recent past, so the disease can be categorized under the emerging status.…”
Section: Discussioncontrasting
confidence: 71%
“…Level of parasitemia (5.9%) shown by Ashuma et al . [14] was found to be on higher side as compared to parasitemia in the present study (0.9%). There was no characteristic difference in the level of parasitemia and clinical manifestation.…”
Section: Discussioncontrasting
confidence: 42%
“…It was found that the calves were 3.62 and 2.53 times more susceptible when compared to adult cows for A. marginale and Babesia sp., respectively. Similar results were observed for A. marginale by Ashuma et al (2013). The results of this paper disagree with Terkawi et al (2012) that found greater positivity of Babesia in adult cattle.…”
Section: Discussioncontrasting
confidence: 58%
“…Bovine anaplasmosis is a severe disease of cattle, characterised by haemolytic anaemia and causes significant economic loss (Ashuma et al, 2013). The losses are as a result of reduction in milk production, increased cost of treatment and management of the disease condition.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%